Day 2 Wed, February 05, 2020 2020
DOI: 10.2118/199722-ms
|View full text |Cite
|
Sign up to set email alerts
|

Use of Reservoir Simulation to Forecast Field EOR Response - An Eagle Ford Gas Injection Huff-N-Puff Application

Abstract: Enhanced oil recovery in unconventional plays has been a focus of many E&P operators to increase recovery factors. Conventional displacement-based secondary (e.g. water flooding) and tertiary EOR methods are not viable options due to their low injectivity in these ultra-low permeability formations. As such, huff-n-puff (HnP) EOR techniques involving field gas injection may be the most effective EOR methods to increase the recovery factors from these shale formations. Several numerical reservoir simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The CO2 diffusive mass transfer would be predominant in shale oil reservoirs 48 . However, previous studies for CO2 interactions in shale oils have considered phase behaviour pertinent to direct contact between CO2 and oil 4,10,33,35,54,55 . Therefore, it appears that, a comprehensive analysis of CO2 diffusive mass transfer in shale oil is needed to highlight the role of gas liberation mechanism during diffusion of CO2 in shale oil.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO2 diffusive mass transfer would be predominant in shale oil reservoirs 48 . However, previous studies for CO2 interactions in shale oils have considered phase behaviour pertinent to direct contact between CO2 and oil 4,10,33,35,54,55 . Therefore, it appears that, a comprehensive analysis of CO2 diffusive mass transfer in shale oil is needed to highlight the role of gas liberation mechanism during diffusion of CO2 in shale oil.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, numerous numerical and simulation studies have been performed on the interactions between CO2 and shale oil formations during huff-n-puff scenarios 4,10,18,32,33 . The fluid model used in these past studies do not capture the mechanism of in-situ gas liberation 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the role of the injection rate and pressure has also been investigated in numerous research studies (Monger and Coma, 1988;Monger et al, 1991;Shayegi et al, 1996;Song and Yang, 2013;Wang et al, 2013;Yu et al, 2014;Sanchez-Rivera et al, 2015;Wan et al, 2015;Sun et al, 2016;Zhang et al, 2018). Wan et al (2018) and Kerr et al (2020) both showed that higher injection pressure and larger slug size would lead to an increase in the recovery factor (Wan et al, 2018;Kerr et al, 2020). Field and laboratory data indicated that the larger slug size improves oil production (Monger and Coma, 1988;Monger et al, 1991;Cronin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They have far less porosity and permeability. Also, they require stimulation and other conversion or extraction techniques such as enhanced oil recovery (EOR) for a feasible production (Zou et al 2013a;Sprunger et al 2021;Syed et al 2021a;Kerr et al 2020;Li et al 2019a;Hawthorne et al 2019;Jin et al 2019). This makes them economically far more expensive than conventional methods.…”
Section: Introductionmentioning
confidence: 99%